Parametric Study of Pile Response to Side-by-Side Twin Tunneling in Stiff Clay - Mangi, N.; Bangwar, D. K.; Karira, H.; Kalhoro, S.; Siddiqui, G. R. (Engineering, Technology & Applied Science Research, 2020)
A three dimensional coupled-consolidation numerical parametric study was carried out in order to gain new insight of single pile response to side-by-side twin tunneling in saturated stiff clay. An advanced hypo plasticity (clay) constitutive model with small-strain stiffness was adopted. The effects of relative to the pile tunnel depths were investigated by simulating the twin tunnels near the pile at various depths of tunnels, namely near the pile shaft, adjacent to the pile toe, and below the pile toe. It was found that the second tunneling in each case resulted in a larger settlement than the one due to the first tunneling with a maximum percentage difference of 175% in the case of twin tunneling near the mid-depth of the shaft. This occurred due to the degradation of clay stiffness around the pile during the first tunneling. Conversely, the first tunneling-induced bending moment was reduced substantially during the second tunneling. The most critical location of twin tunnels relative to the pile was found to be below the pile toe.